"Emotional Distancing": Change and Strain in U.S. Young Adult College Students' Relationships During COVID-19. Issue 2 (April 2022) - Dotson, Miranda P.; Castro, Elena Maker; Magid, Nina T.; Hoyt, Lindsay T.; Suleiman, Ahna Ballanoff; Cohen, Alison K.
We analyzed qualitative data from 707 USA college students aged 18–22 in late April 2020 regarding if and how their relationships had changed at the start of the COVID-19 pandemic. Most (69%) participants experienced relationship changes, most of whom (77%) described negative changes: less overall contact, feeling disconnected, and increased tension, some of which was due to conflict over pandemic-related public health precautions. Physical distancing from social contacts also created emotional distancing: it was harder to maintain affective connections via online platforms and within the isolating context of shelter-in-place. Due to emerging adulthood being a sensitive window for social development, the COVID-19 pandemic-induced emotional distancing could have long-term ramifications for this cohort's relationships over the course of their lives.